Apathy in individuals with Parkinson's disease associated with mild cognitive impairment. A neuropsychological investigation. (September 2018) - Costa, Alberto; Peppe, Antonella; Zabberoni, Silvia; Scalici, Francesco; Caltagirone, Carlo; Carlesimo, Giovanni Augusto
Abstract: Apathy is frequently reported in individuals with Parkinson's disease (PD) and is hypothesized to be associated with frontal-striatal related cognitive functions. Available data, however, do not provide univocal results. Moreover, this relationship has been poorly investigated in PD patients with mild cognitive impairment (MCI). This study was aimed at investigating the association between severity of apathy of PD patients and their performance on neuropsychological tests investigating executive abilities. Individuals with PD (i.e., with and without MCI) and healthy controls (HCs) were administered a neuropsychological test battery that investigated episodic memory, language, short-term memory and attention, visual-spatial abilities and executive functions. Subjects were also administered additional neuropsychological tests to evaluate the different executive subcomponents (i.e., planning/abstract reasoning, self-monitoring/response inhibition, working memory, shifting and fluency). The Apathy Evaluation Scale (AES) was administered to assess apathy severity. Linear regression analyses were applied to the data; results showed that in the PD group with MCI, the best cognitive factor associated to the AES score was patients' scores on the executive tests and, in particular, their scores on tests examining planning/abstract reasoning. By contrast, in the PD group without MCI, the cognitive performance was not significantly associated to apathy severity. Findings of the study document a specific association between reduced efficiency of the executive system and apathy severity in individuals with PD and MCI. This association indirectly supports the hypothesis of a relationship between motivational disorders and dysregulation of the activity of the frontal-striatal networks in PD patients. Highlights: The association between cognitive disorders and apathy is proposed. Executive functioning predicts apathy severity in Parkinson's disease. The involvement of frontal-striatal dysregulation in apathy is suggested.